Effects of a Chronic Oil Spill on the Planktonic System in San Jorge Gulf, Argentina: A One-Vertical-Dimension Modeling Approach - Klotz, Philippe (2018)
Known for its high biological productivity, San Jorge Gulf (SJG) in Argentinian Patagonia is also an area of oil exploitation. To understand the dynamics of the SJG plankton ecosystem under several scenarios of potential hydrocarbon (HC) contamination, we present an 11-compartment biogeochemical model coupled to a turbulence model. In the coupled model, we parameterize the main physical and biological processes related to HC contamination, such as biodegradation, growth, and mortality of phyto-, zoo-, and bacterioplankton. Planktonic responses to several levels of HC contamination are studied for two physically contrasting SJG environments, a tidally well-mixed water column and a stratified water column. Results show increasing phyto-and bacterioplankton biomass with increasing HC concentration, which in turn produces more detritus. Zooplankton communities seem to respond differently depending on HC concentration, with major indirect changes occurring in the different size classes. Effects of HC contamination on biological compartments are stronger in the stratified than in the well-mixed environment.